Frequency of Elevated Levels of Serum CRP in Patients with Preterm Labor in a Tertiary Care Hospital, Karachi - Sadia Detho, Aneela Habib, Saima Aziz, Urooj Naz, Aruna Kumari Hira, Sarah Kazi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Preterm birth is a significant public health problem, occurring in over 10 percent of births world wise, and contributing largely to neonatal mortality and various morbidities in childhood and later in life. Increase level of C-reactive protein (CRP) is associated with increased risk of preterm delivery. This study is designed to determine the elevated level of CRP in patients with preterm labor to establish a local data. Results of my study can be grate help for other care health provider to provide effective antenatal care. Objective: To determine frequency of elevated levels of serum CRP (by blood serum test) in patients with preterm labor in a tertiary care hospital, Karachi. Setting: This Cross Sectional Study was conducted in the Department of Obstetrics and gynecology, Civil hospital Karachi for the duration of six months from January, 2018 to July, 2018. Subject and Methods: A total of 88 pregnant women with pre term delivery were included in this study. Preterm labor was confirmed by uterine contraction (3 contraction in 10 minutes each lasting for 30 second) and cervical dilatation of preterm labor. Blood sample was taken for CRP level whole of this information was documented on predesigned proforma. Results: The average age of the women was 28.26±4.02 years. Frequency of elevated level of serum CRP in patients with preterm labor was 89.77% (79/88). Conclusion: In present study frequency of elevated level of serum CRP in patients with preterm labor was 89.77%. Measurement of the C-reactive protein during pregnancy can be used as a predictive screening biomarker for detection of subclinical infections that cause preterm uterine contraction and hence early intervention and intensive antenatal care to reduce the perinatal morbidity and mortality.